2021
DOI: 10.1021/acscatal.0c03725
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometric Study of Electrochemical CO2 Reduction on Pd and Pd-B Electrodes

Abstract: The electrochemical CO2 reduction reaction (CO2RR) on Pd-based electrodes to dissolved formate and/or gaseous CO is largely dependent on potential and the electrode material, yet there is a lack of molecular-level insights into this dependence. Herein, in situ attenuated total reflection surface enhanced infrared absorption spectroscopy (ATR-SEIRAS) in conjunction with differential electrochemical mass spectrometry (DEMS), gas chromatography (GC), and nuclear magnetic resonance (NMR) measurements is applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 59 publications
1
64
0
Order By: Relevance
“…[129,130] In addition, doping B into Pd-based electrocatalysts equally becomes a universal approach to deliberately regulate the electronic structure and enhance their electrocatalytic performance. [131,132] It should be emphasized that doping B could generally cause the downshift of the d-band center derived from the electron transfer between the d-orbitals of Pd and p-orbitals of B. As demonstrated by Sato and coworkers, B-doped Pd could decrease the barrier of O 2 dissociation and optimize the binding energy of ORR intermediates, recognizing that Pd-B is highly active for ORR in alkaline media (Figure 4d).…”
Section: Heteroatom Dopingmentioning
confidence: 95%
“…[129,130] In addition, doping B into Pd-based electrocatalysts equally becomes a universal approach to deliberately regulate the electronic structure and enhance their electrocatalytic performance. [131,132] It should be emphasized that doping B could generally cause the downshift of the d-band center derived from the electron transfer between the d-orbitals of Pd and p-orbitals of B. As demonstrated by Sato and coworkers, B-doped Pd could decrease the barrier of O 2 dissociation and optimize the binding energy of ORR intermediates, recognizing that Pd-B is highly active for ORR in alkaline media (Figure 4d).…”
Section: Heteroatom Dopingmentioning
confidence: 95%
“…Further spectrometric study via various in situ measurements, such as attenuated total reflection surfaceenhanced infrared absorption spectroscopy (ATR-SEIRAS) in conjunction with differential electrochemical mass spectrometry (DEMS), nuclear magnetic resonance (NMR) and gas chromatography (GC), proved that B doping of Pd could hinder the CO formation and promote formate production on the Pd-B electrode compared with the original Pd electrode in all of the investigated potential ranges during the CO 2 RR process. 148 Other atom doping still needs to be studied by combining the electrochemical measurements, in situ spectrometric technologies, and theoretical calculations to unveil the effect of nonmetallic atom doping on the electronic structure of Pd, the intermediates and the final products.…”
Section: Pdl X For Electrochemical Co 2 Rrmentioning
confidence: 99%
“…The physical and chemical properties of metalloid elements are between those of metals and nonmetals. In noble metal–metalloid alloys, the introduction of metalloids endows noble metal catalyst materials with different surface electronic structures and geometric properties (compared to metal–metal alloys and metal–nonmetal alloys). Boron (B) is the primary metalloid element developed for alloys, and it exhibits a good diversity of compositions and structures in noble metal–B alloys. , Theoretical studies have shown that the metal–B electron interactions in boron-containing intermetallic compounds have a positive effect on surface hydrogen adsorption and, thus, boost the catalytic activity of the compounds in hydrogen evolution. The modulation of this electronic structure makes several intermetallic compounds ( e.g ., PdB, RuB, ReB) promising and efficient hydrogen evolution materials with catalytic activity beyond Pt .…”
Section: Synthetic Strategies For Mesoporous Noble Metal–metalloid Al...mentioning
confidence: 99%